2020
DOI: 10.2337/dc19-1480
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CXCR1/2 Does Not Improve Insulin Secretion After Pancreatic Islet Transplantation: A Phase 3, Double-Blind, Randomized, Placebo-Controlled Trial in Type 1 Diabetes

Abstract: Reparixin is an inhibitor of CXCR1/2 chemokine receptor shown to be an effective anti-inflammatory adjuvant in a pilot clinical trial in allotransplant recipients. RESEARCH DESIGN AND METHODSA phase 3, multicenter, randomized, double-blind, parallel-assignment study (NCT01817959) was conducted in recipients of islet allotransplants randomized (2:1) to reparixin or placebo in addition to immunosuppression. Primary outcome was the area under the curve (AUC) for C-peptide during the mixed-meal tolerance test at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…IAK was associated with better glucose control and a slower decrease in eGFR than standard insulin therapy in patients with type 1 diabetes and a functioning kidney transplant (Maanaoui et al, 2020). In this first doubleblind randomized trial, the islet transplant evidence obtained with reparixin does not support the role of CXCR1/2 inhibition in preventing inflammationmediated damage to the islet (Maffi et al, 2020).…”
Section: Islet Transplantationmentioning
confidence: 85%
“…IAK was associated with better glucose control and a slower decrease in eGFR than standard insulin therapy in patients with type 1 diabetes and a functioning kidney transplant (Maanaoui et al, 2020). In this first doubleblind randomized trial, the islet transplant evidence obtained with reparixin does not support the role of CXCR1/2 inhibition in preventing inflammationmediated damage to the islet (Maffi et al, 2020).…”
Section: Islet Transplantationmentioning
confidence: 85%
“…Islet engraftment and function was assessed on day 75 ± 5 after islet infusion using the mixed meal tolerance test (MMTT) 8 . Patients were followed for 1 year after the last islet infusion 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Reparixin is a potent CXCR1/2 inhibitor and thus it was hypothesized that it could limit IBMIR and improve islet engraftment. Despite success in preclinical and single center clinical studies 3 5 , a recent phase 3 multicenter trial did not confirm this beneficial effect of Reparixin. However, the trial was performed without the standardization of donor selection, islet processing, and immunosuppression regimens among the participating centers 5 .…”
Section: Introductionmentioning
confidence: 99%
“…This treatment opportunity should be tested in patients with COVID‐19 at the time of hospital admission to halt or decrease progression of respiratory insufficiency and prevent the need for intensive care support 20 . Considering other treatments under evaluation to avoid IBMIR in islet transplantation (although not yet commercially available) the chemokine receptor 2 (CXCR2) inhibitor reparixin appears of interest 21,22 . In fact, numerous studies have confirmed a key role of CXCR1/CXCR2 receptor as potential therapeutic target in acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) 23,24 .…”
Section: Microvascular Covid‐19 Lung Vessels Obstructive Thrombo‐inflmentioning
confidence: 99%